Non-oriented electrical steel under bending and annealing effects - Hebri, Mohamed Amine; Bauw, Grégory; Lecointe, Jean-Philippe; Duchesne, Stéphane; Fawaz, Sara; Zito, Gianluca; Arslane, Idir; Abdelli, Abdenour; Maier, Adrien; Vandeginen, Clément (Archives of Electrical Engineering (Online), 2025)
This study investigates the impact of bending stress and annealing on the mag- netic performance of 3% silicon-iron non-oriented electrical steel (NOES). Samples were bent into diameters of 120 mm, 160 mm, and 200 mm representing the internal, average and external diameters of an axial flux machine and their magnetic properties, including permeability and iron losses, were measured. The results show that bending stress signifi- cantly degrades these properties, with smaller diameters causing greater deterioration. An- nealing treatments were applied to restore performance, with partial or full recovery de- pending on the annealing temperature. A finite element (FE) model is proposed to account for the effects of bending on magnetic performance, incorporating three regions with dis- tinct magnetic properties corresponding to different bending radii, using the commercial software JMAG-Designer. The study's findings provide valuable insights into the effects of bending and annealing on NOES, offering potential applications in toroidal transformers and axial flux machines.